mt3sol - Homework 3, Math 245, Fall 2010 Due Friday,...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
Homework 3, Math 245, Fall 2010 Due Friday, October 1 in class. The solution of each exercise should be at most one page long. If you can, try to write your solutions in LaTex. Each question is worth 2 points. 1. The Fibonacci numbers ( F n ) n 1 are defined as follows: F 1 = F 2 = 1 and F n = F n - 1 + F n - 2 for every n 2. Prove that F n = ± 1+ 5 2 ² n - ± 1 - 5 2 ² n 5 for every n 1. Proof. We will use strong induction on n to prove that F n = ± 1+ 5 2 ² n - ± 1 - 5 2 ² n 5 . Base Case: n = 1. In this case, F 1 = 1 and ± 1+ 5 2 ² 1 - ± 1 - 5 2 ² 1 5 = 2 5 2 5 = 1. n = 2. In this case, F 2 = 1 and F 2 = ± 1+ 5 2 ² 2 - ± 1 - 5 2 ² 2 5 = 6+2 5 4 - 6 - 2 5 4 5 = 4 5 4 5 = 1 . Thus, the base case is true. Induction Step: Assume that F i = ± 1+ 5 2 ² i - ± 1 - 5 2 ² i 5 for every i , 1 i k . We will prove that F k +1 = ± 1+ 5 2 ² k +1 - ± 1 - 5 2 ² k +1 5 (1)
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Using the recurrence relation of the Fibonacci numbers and the induction hypothesis, we get F k +1 = F k + F k - 1 = ± 1+ 5 2 ² k - ± 1 - 5 2 ² k 5 + ± 1+ 5 2 ² k - 1 - ± 1 - 5 2 ² k - 1 5 = ± 1+ 5 2 ² k + ± 1+ 5 2 ² k - 1 5 - ± 1 - 5 2 ² k + ± 1 - 5 2 ² k - 1 5 = ± 1+ 5 2 ² k - 1 ± 1+ 5 2 + 1 ² 5 - ± 1 - 5 2 ² k - 1 ± 1 - 5 2 + 1 ² 5 = ± 1+ 5 2 ² k - 1 · 3+ 5 2 5 - ± 1 - 5 2 ² k - 1 · 3 - 5 2 5 = ± 1+ 5 2 ² k - 1 · 6+2 5 4 5 - ± 1 - 5 2 ² k - 1 · 6 - 2 5 4 5 = ± 1+ 5 2 ² k - 1 · ± 1+ 5 2 ² 2 5 - ± 1 - 5 2 ² k - 1 · ± 1 - 5 2 ² 2 5 = ± 1+ 5 2 ² k +1 5 - ± 1 - 5 2 ² k +1 5 . This finishes our proof. 2. Let f : A B and g : B C be two functions. Show that if g f is injective, then f is injective. Show that if g f is surjective, then g is surjective. Proof. First, we show that if g f is injective, then f injective. Let a,b A such that f ( a ) = f ( b ). Applying g to both sides we obtain g ( f ( a )) = g ( f ( b )) which means ( g f )( a ) = ( g f )( b ). As g f is injective, this implies a = b and shows f is injective. Secondly, we show that if g f is surjective, then g is surjective. Let
Background image of page 2
Image of page 3
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 12/07/2011 for the course MATH 245 taught by Professor Cioaba during the Fall '10 term at University of Delaware.

Page1 / 6

mt3sol - Homework 3, Math 245, Fall 2010 Due Friday,...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online